How the Experimental Setting Influences Representativeness: A Review of Gaze Behavior in Football Penalty Takers - Kurz, Johannes; Munzert, Jörn (Frontiers in Psychology, 2018)
This article reviews research on the gaze behavior of penalty takers in football. It focuses on how artificial versus representative experimental conditions affect gaze behavior in this far-aiming task. Findings reveal that—irrespective of the representativeness of the experimental conditions—different instructions regarding the aiming strategy and different threat conditions lead to different gaze patterns. Results also reveal that the goal size and the distance to the goal did not affect the gaze behavior. Moreover, it is particularly run-up conditions that lead to differences. These can be either artificial or more natural. During a natural run-up, penalty takers direct their gaze mainly toward the ball. When there is no run-up, they do not direct their gaze toward the ball. Hence, in order to deliver generalizable results with which to interpret gaze strategies, it seems important to use a run-up with a minimum length that is comparable to that in a real-life situation.